Response of growing goslings to dietary supplementation with methionine and betaine. Issue 6 (1st November 2016) - Yang, Z.; Wang, Z.Y.; Yang, H.M.; Zhao, F.Z.; Kong, L.L.
Abstract: An experiment with a 2 × 3 factorial design with two concentrations of dietary betaine (0 and 600 mg/kg) and three dietary concentrations of methionine (0, 600 and 1200 mg/kg) was conducted using goslings to estimate growth, nutrient utilisation and digestibility of amino acids from 21 to 70 d of age. Three hundred geese were randomised at 18 d of age into 6 groups with 5 replicates per treatment and 10 geese per replicate. Increasing dietary concentrations of methionine gave a linear increase in body weight and average daily gain. The coefficient of crude fat retention increased as dietary methionine increased and there was a significant non-linear response to increasing dietary methionine. Similarly, increasing supplemental methionine gave linear increases in the digestibility of methionine and cysteine. The results of this study indicated that optimal dietary supplementation of methionine could increase growth performance and methionine and cysteine utilisation in growing goslings. Betaine supplementation had no apparent sparing effect on methionine needs for growth performance, but did improve the apparent cysteine digestibility.